Predicting recycling behavior using the theory of planned behavior. - Celebria, Carl Gil Angelo H. (2015.)
The study investigated the relationship between awareness of climate change and the three predictors of intention to recycle: attitude towards recycling, subjective norm and perceived behavioral control. The study also explored the applicability of the theory pf planned behavior (TBP) to predict recycling behavior. To examine these relationships, 70 government employees from different offices of the Iloilo Provincial Capitol were surveyed. Awareness of climate change scale was used to measure their level of awareness about climate change. A TBP questionnaire on Recycling was used to measure their attitude towards recycling, subjective norm and perceived behavioral control of recycling, intention to recycle. Last a Recycling Behavior scale was used to measure the participants recycling behaviors. Using correlation and regression analysis, results showed that awareness of climate change had no relationship with attitude towards recycling, subjective norm and perceived behavioral control. However, attitude recycling and perceived behavioral control had a significant relationship with intention to recycle. Furthermore, intention to recycle predicted the respondent's recycling behavior.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Planned Behavior -- Theory